Research on Information Security Mechanism Used in Network Video Surveillance System - Yanxia Zhang; Hong Li; Jun Chen; Xiaoguang Yang (Dianxin kexue)
Information security mechanism is a key part of security network video surveillance system,including service data security and multimedia data security,and there are a lot of security solutions and specifications now.Two typical specifications on the network video surveillance system were selected to analyze their information security mechanism and the encryption algorithm,and the suggestions on common data protection mechanism were given out.